Synthesis of small-sized platinum nanobelts by a simple one-step solvothermal method and application
Patent Information
- Application Number
- CN202611015139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-09-15
Smart Images

Figure CN122746474A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterial synthesis and relates to a method for synthesizing nanoribbons using a simple solvothermal method. Background Technology
[0002] Among various platinum nanostructures, low-dimensional (LW) nanostructures, typically one-dimensional and two-dimensional, have attracted considerable attention due to their unique morphology. They provide abundant exposed surface areas for catalytic active centers and improve structural integrity, thus aiding in Ostwald ripening and dissolution. (Shao, Q.; Wang, P.; Zhu, T.; Huang, X., Low Dimensional Platinum-Based Bimetallic Nanostructures for Advanced Catalysis. Accounts of Chemical Research 2019, 52 (12), 3384-3396.) For example, Yamauchi et al. prepared centimeter-scale self-supporting 2D ultrathin mesoporous platinum nanosheets with an electrochemically active surface area 2.4 times that of commercial platinum black. The nanosheets exhibited superior methanol oxidation and oxygen reduction performance compared to platinum / carbon, with only half the half-wave potential decay after 5000 cycles, demonstrating excellent stability and electrocatalytic performance. (Li, Y.; Liu, Y.;Li, J.; Xiong, D.; Chen,
[0003] Since the synthesis of zinc, tin, indium, cadmium, and gallium semiconductor oxide nanoribbons in 2001, one-dimensional nanoribbons, or nanobelts, have attracted widespread attention because they provide an ideal system for a comprehensive understanding of the electrical, thermal, optical, and ion transport processes in one-dimensional nanostructures and for constructing functional devices along individual nanoribbons. Many successful routes have been explored for the synthesis of oxide, sulfide, and carbon nanoribbons. However, reports on the synthesis of metallic nanoribbons are scarce. Due to their more defined sides, the growth of metallic crystals is generally higher than that of oxide nanoribbons. Therefore, the formation of metallic nanoribbons is much more difficult.
[0004] Therefore, considering the limitations of reaction conditions on the synthesis of platinum nanoribbons, various chemical methods have been developed for synthesis. However, due to the anisotropy of Pt metal growth and its difficult-to-reduce nature, the synthesis of high-quality platinum nanowires in solution under simple reaction conditions remains a huge challenge. Summary of the Invention
[0005] The purpose of this invention is to provide a simple one-pot method for synthesizing small-sized platinum nanoribbons. The nanoribbons mostly exhibit elongated trapezoidal, twisted hexagonal, and square shapes. The longitudinal dimension of the nanoribbons varies considerably, ranging from 20 nm to 2 nm, while the width is relatively uniform, with an average width of 8.1 ± 1.9 nm.
[0006] This invention utilizes a solvothermal method. Under the action of a solvent and a reducing agent, platinum nanoparticles, platinum nanowires, and platinum nanoribbons can be obtained by changing the reaction time and temperature. Changing the concentration of the solvent DETA alters the ratio between wires and ribbons, and adjusting the concentration of the solvent diethylenetriamine and the content of the reducing agent molybdenum hexacarbonyl can control the width of small-sized platinum nanoribbons. Furthermore, the precipitate is washed, dried, and mixed with carbon powder to create an ink, which is then loaded onto a working electrode, showing great potential for application in ethylene glycol electrocatalysis. This invention features a simple process, mild reaction conditions, low cost, and the advantages of precise controllability, ease of operation, and environmental friendliness in the solvothermal synthesis of nanomaterials. This invention enables the direct synthesis of nanoribbons in the solution phase, overcoming the limitations of complex traditional hydrothermal synthesis methods and solving the problem of morphological changes caused by template removal. It demonstrates great application prospects in electrocatalysis, organic catalysis, and optoelectronic devices.
[0007] To solve the technical problem of this invention, the proposed technical solution includes the following steps: a simple one-step solvothermal method for synthesizing small-sized platinum nanoribbons, comprising the following steps:
[0008] (1) Platinum acetylacetonate Pt(acac)2 and molybdenum hexacarbonyl Mo(CO)6 were uniformly dispersed in diethylenetriamine DETA, with final concentrations of 2.12 mM and 18.93 mM, respectively;
[0009] (2) Transfer the ultrasonically dispersed solution from step (1) to a Teflon-lined autoclave and heat it at 150-240°C for 3-6 hours.
[0010] (3) Take out the precipitate after the reaction in step (2), wash it with ethanol and water several times to obtain platinum nanoribbons.
[0011] Preferably, in step (1), 5 mg of Pt(acac)2 and 30 mg of Mo(CO)6 solid powder are simultaneously added to 6 ml of diethylenetriamine DETA;
[0012] Step (2) Transfer the liquid to a 10 mL Teflon-lined autoclave and heat it at 200°C for 3 hours. DETA can be adsorbed onto the platinum surface through reaction.
[0013] Preferably, the nanoribbons are mostly elongated trapezoids, twisted hexagons, and squares; the longitudinal direction of the nanoribbons varies greatly, from 20 nm to 2 nm, and the width is relatively uniform, with an average width of 8.1 ± 1.9 nm;
[0014] The precipitate after the reaction in step (2) was removed, washed repeatedly with ethanol and water, and then characterized.
[0015] Preferably, it includes the following steps:
[0016] (1) 5 mg of Pt(acac)2 and 30 mg of molybdenum hexacarbonylMo(CO)6 were uniformly dispersed in 6 mL of diethylenetriamine (DETA) and the final concentrations were 2.12 mM and 18.93 mM, respectively;
[0017] (2) Transfer the ultrasonically dispersed solution from step (1) to a 10 ml Teflon-lined autoclave and heat it at 150°C for 6 hours.
[0018] (3) Take out the precipitate after the reaction in step (2), wash it with ethanol and water several times, and then characterize it.
[0019] Preferably, it includes the following steps:
[0020] (1) 5 mg of Pt(acac)2 and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of diethylenetriamine DETA, and the final concentrations were 2.12 mM and 18.93 mM, respectively;
[0021] (2) Transfer the ultrasonically dispersed solution from step (1) to a 10 ml Teflon-lined autoclave and heat it at 240°C for 3 hours.
[0022] (3) Take out the precipitate after the reaction in step (2), wash it with ethanol and water several times, and then characterize it.
[0023] To address the technical problem of this invention, another technical solution is proposed: the platinum nanoribbons prepared by the method can be used in fuel cells or electrochemical catalysis.
[0024] Preferably, the synthesized platinum nanoribbon black precipitate is dried, mixed with carbon powder, and loaded onto a 3 mm diameter disc working electrode for catalytic testing.
[0025] Preferably, due to its unique structural features, this ribbon structure can be used in ethylene glycol fuel cells or proton exchange membrane batteries, exhibiting good electrocatalytic activity.
[0026] Beneficial effects:
[0027] Compared with existing technologies, this invention enables the direct synthesis of platinum nanoribbons in solution phase, and directly uses diethylenetriamine as a surfactant and ligand to eliminate the influence of solvents, with a maximum nanometer size of approximately 20 nm. This technology overcomes the limitations of complex solvothermal synthesis methods and solves the problem of nanoribbon morphology changes caused by template removal, showing great application potential in fields such as electrocatalysis, organic catalysis, and optoelectronic devices.
[0028] The platinum nanoribbons prepared by this invention have unique structural features, and this ribbon structure can be used in fuel cells such as ethylene glycol fuel cells and proton exchange membrane batteries, exhibiting good electrocatalytic activity.
[0029] This method is simple to operate and significantly reduces the risks associated with traditional, complex methods for synthesizing platinum nanosheets or nanoribbons. Furthermore, the synthesis ratio of platinum nanoribbons can be controlled by altering the concentrations of the solvent and the surfactant DETA. This offers great application potential for fields such as electrocatalysis. The process is simple and inexpensive.
[0030] This technology only requires the metal precursor platinum acetylacetonate (Pt(acac)2), the reducing agent Mo(CO)6, and the solvent diethylenetriamine (DETA), which also acts as a surfactant. Therefore, the concentrations of the reducing agent and the solvent in this technology need to be further controlled.
[0031] In step (1), the amount of DETA can be changed by adding oleylamine to dilute DETA, which can change the yield of platinum nanoribbons.
[0032] At a concentration of 2.12 mM platinum acetylacetonate (Pt(acac)2), we determined the optimal reduction conditions for solvothermal growth: a reducing agent concentration of approximately 18.93 mM, a reaction temperature of 200 °C, and a reaction time of 3 hours. Figure 1 As shown, within this window, the synthesized platinum nanoribbons can fully exhibit their ribbon-like structure.
[0033] In this invention, we conducted a comparative study on the reducing agents and solvent concentrations that affect the formation of platinum nanoribbons. The product was analyzed by transmission electron microscopy, such as... Figure 2As shown, when the DETA / OAM ratio is 1:5, reducing the amount of Mo(CO)6 to 5 mg results in a large number of wire-plate hybrid nanostructures. Similarly, when the DETA / OAM molar ratio is 1:1, increasing Mo(CO)6 to 50 mg primarily produces nanowire products. It was also found that the size of the nanoplates gradually increases with increasing DETA concentration. When 5 mg of Mo(CO)6 is added, the average diameter of the sheet-like structures increases from 5.1 nm to 7.1 nm and 10.5 nm as the DETA / OAM ratio increases from 1:5 to 1:1 and 5:1, respectively. Overall, high concentrations of Mo(CO)6 control the one-dimensional growth of platinum crystals, while high concentrations of DETA promote two-dimensional growth.
[0034] However, when other solvents, such as oleylamine, are introduced to reduce the volume ratio of diethylenetriamine, one-dimensional platinum nanowires are always formed. Therefore, we use pure DETA as the solvent to avoid the influence of solvent-induced degradation. Furthermore, the presence of a large amount of molybdenum hexacarbonyl does not result in two-dimensional banded morphology; instead, nanowire products are mainly formed. Therefore, we do not use large amounts of molybdenum hexacarbonyl (Mo(CO)6) in our system, as excessively low Mo(CO)6 concentrations primarily result in sheet-like structures. A balance among the three is required, with the optimal combination being 30 mg of molybdenum hexacarbonyl (Mo(CO)6), pure diethylenetriamine, and 5 mg of platinum acetylacetone. Attached Figure Description
[0035] Figure 1 Transmission electron microscope image of platinum nanoribbons prepared according to the present invention (a); X-ray diffraction pattern of platinum nanoribbons; (c, d) HRTEM image of a single platinum nanoribbon (inset: corresponding FFT pattern).
[0036] Figure 2 TEM image of longer platinum nanoribbons
[0037] Figure 3 Different reducing agents were used: (a) glucose, (b) ethylene glycol.
[0038] Figure 4 Different amines were used as solvents and surfactants: (a) ethylenediamine, (b) ethylenediaminetetraacetic acid, (c) pentaethylenehexamine, (d) oleylamine.
[0039] Figure 5 TEM images of 3 mg of platinum acetylacetonate (Pt(acac)2) and 5 mg of potassium chloroplatinate.
[0040] Figure 6TEM images of platinum nanocrystals synthesized by immobilizing diethylenetriamine and oleylamine in molybdenum hexacarbonyl solutions of different concentrations at ratios of 1:5, 1:1, and 5:1. (a, c, e) 5 mg molybdenum hexacarbonyl; (b, d, f) 50 mg molybdenum hexacarbonyl.
[0041] Figure 7 statistics Figure 6 The diameter of small-sized platinum nanoribbons (a, c, e).
[0042] Figure 8 Platinum nanocrystals were prepared by using different volume ratios of diethylenetriamine (DETA) and oleylamine (OAm) under the condition of 30 mg molybdenum hexacarbonyl (Mo(CO)6).
[0043] Figure 9 TEM images of platinum nanocrystals obtained at different reaction times: (a) 30 min; (b) 45 min; (c) 60 min; (d) 2.5 h; (e) 3 h; (f) 6 h.
[0044] Figure 10 Transmission electron microscopy (TEM) images of platinum nanocrystals prepared at 150 °C for different reaction times: (a) 1 hour; (b) 2 hours; (c) 3 hours; (d) 6 hours
[0045] Figure 11 TEM images of platinum nanocrystals synthesized using different reaction temperatures in this invention: (a) 120 ℃; (b) 150 ℃; (c) 160 ℃; (d) 180 ℃; (e) 200 ℃; (f) 240 ℃.
[0046] Figure 12 The reaction was carried out at 150 °C for 3 hours, then transferred to 200 °C for another 3 hours.
[0047] Figure 13 Fourier transform infrared spectroscopy of DETA adsorption
[0048] Figure 14 The area activity map was obtained by cyclic voltammetry (CV) when platinum nanoribbons on the supported working electrode and conventional commercial platinum carbon were used as ethylene glycol oxidation catalysts.
[0049] Figure 15 The stability of platinum nanoribbons on the loaded working electrode and conventional commercial platinum-carbon as ethylene glycol oxidation catalysts was measured by chronocurrent (it) stability test results. Detailed Implementation
[0050] The present invention will be further described below with reference to specific embodiments and accompanying drawings.
[0051] Example 1
[0052] (1) Platinum nanoribbons were first synthesized by a solvothermal method. Typically, 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of DETA, with final concentrations of 2.12 mM and 18.93 mM, respectively.
[0053] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat at 200°C for 3 hours.
[0054] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0055] Figure 1 Transmission electron microscope image of platinum nanoribbons prepared according to the present invention (a); X-ray diffraction pattern of platinum nanoribbons; (c, d) HRTEM image of a single platinum nanoribbon (inset: corresponding FFT pattern).
[0056] Figure 2 TEM image of longer platinum nanoribbons
[0057] The product was analyzed using a transmission electron microscope. Figure 1 The nanoribbons shown in figure a mostly exhibit elongated trapezoidal, twisted hexagonal, and square shapes. The longitudinal variation of the nanoribbons is significant, with some reaching 20 nm, but the width is relatively uniform, with an average width of 8.1 ± 1.9 nm. (X-ray diffraction pattern) Figure 1 b). The results show that the platinum nanoribbons possess a typical face-centered cubic (FCC) platinum lattice (JCPDS NO.04-0802). The detailed crystal structure of the nanoribbons was further characterized using high-resolution electron microscopy (HRTEM). Figure 1 c shows an HRTEM image of a twisted hexagonal nanoplate. Two sets of characteristic lattice fringes with interplanar spacings of 0.196 nm and 0.135 nm can be pointed to the (200) and (220) crystal planes of the face-centered cubic platinum lattice, respectively. Square fast Fourier transform (FFT) plots and corresponding selected area electron diffraction (SAED) patterns further indicate that the incident electron beam is along the
[100] region axis of the fcc lattice, suggesting that the two exposed planes of the hexagonal nanoplate have (100) planes. Therefore, the paired parallel sides of the twisted hexagonal nanoplate can be assigned to the (220) (c1 and c4) and (200) (c2, c3, c5 and c6) planes. In addition, other nanoplates with less regular shapes also exhibit similar lattice fringes and FFT patterns. Figure 1d) Verify that the nanoribbons mainly have exposed (100) flat surfaces.
[0058] Example 2
[0059] (1) Disperse 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of glucose and 2 ml of ethylene glycol evenly in 6 mL of DETA;
[0060] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat at 200°C for 3 hours.
[0061] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0062] Figure 3 Different reducing agents were used: (a) glucose, (b) ethylene glycol.
[0063] from Figure 3 It can be seen that not all reducing agents used in combination with DETA and platinum acetylacetonate will result in the formation of two-dimensional platinum nanoribbons.
[0064] Example 3
[0065] (1) 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of ethylenediamine, ethylenediaminetetraacetic acid, pentaethylenehexamine and oleylamine, with final concentrations of 2.12 mM and 18.93 mM, respectively.
[0066] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat at 200°C for 3 hours.
[0067] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0068] Figure 4 Different amines were used as solvents and surfactants: (a) ethylenediamine, (b) ethylenediaminetetraacetic acid, (c) pentaethylenehexamine, (d) oleylamine.
[0069] from Figure 4 It can be seen that not all amine ligands guide the two-dimensional growth of platinum. Ethylenediamine-guided growth does not produce platinum with a specific morphology, ethylenediaminetetraacetic acid (EDTA) guides the formation of particles, and pentaethylenehexamine and oleylamine guide the formation of nanorods. Therefore, diethylenetriamine (DETA) is our preferred solvent and surfactant.
[0070] Example 4
[0071] (1) Disperse 3 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) evenly in 6 mL of DETA;
[0072] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat at 200°C for 3 hours.
[0073] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it;
[0074] Figure 5 TEM images of 3 mg of platinum acetylacetonate (Pt(acac)2) and 5 mg of potassium chloroplatinate.
[0075] Figure 5 The left image is the TEM diagram of the reaction with 3 mg of acetylacetonate platinum. From the image, we can see that due to its low content, it cannot fully exhibit its two-dimensional banded morphology. The right image shows the reaction when acetylacetonate platinum is replaced with potassium chloride platinumate. Since it is a water-soluble drug, it cannot be well integrated in our oily system and no two-dimensional morphology is generated.
[0076] Example 5
[0077] (1) 5 mg of platinum acetylacetonate (Pt(Acac)2) and 5 mg and 50 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in diethylenetriamine: oleylamine in volume ratios of 1:5, 1:1 and 5:1, respectively.
[0078] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat at 200°C for 3 hours.
[0079] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0080] Figure 6 TEM images of platinum nanocrystals synthesized by immobilizing diethylenetriamine and oleylamine in molybdenum hexacarbonyl solutions of different concentrations at ratios of 1:5, 1:1, and 5:1. (a, c, e) 5 mg molybdenum hexacarbonyl; (b, d, f) 50 mg molybdenum hexacarbonyl.
[0081] Figure 7 statistics Figure 6 The diameter of small-sized platinum nanoribbons (a, c, e).
[0082] Transmission electron microscopy analysis of the product revealed that when the DETA / OAM ratio was 1:5, reducing the amount of Mo(CO)6 to 5 mg resulted in a large number of wire-plate hybrid nanostructures. Similarly, when the DETA / OAM molar ratio was 1:1, increasing Mo(CO)6 to 50 mg primarily generated nanowire products. Furthermore, it was found that the size of the nanoplates gradually increased with increasing DETA concentration. When 5 mg of Mo(CO)6 was added, the average diameter of the sheet-like structures increased from 5.1 nm to 7.1 nm and 10.5 nm, respectively, as the DETA / OAM ratio increased from 1:5 to 1:1 and 5:1. Overall, high CO concentration controlled the one-dimensional growth of platinum crystals, while high DETA concentration promoted two-dimensional growth.
[0083] However, when other solvents, such as oleylamine, are introduced to reduce the volume ratio of diethylenetriamine, one-dimensional platinum nanowires are always formed. Therefore, we use pure DETA as the solvent to avoid the influence of solvent-induced degradation. Figure 6 As can be seen from b, d, and f, the presence of a large amount of molybdenum hexacarbonyl does not result in the formation of two-dimensional banded morphology, but mainly generates nanowire products. Therefore, we do not use a large amount of molybdenum hexacarbonyl in our system. If the concentration of Mo(CO)6 is too low, it will mainly generate a sheet-like structure. Instead, a balance is needed among the three. We use 30 mg of molybdenum hexacarbonyl (Mo(CO)6), pure diethylenetriamine, and 5 mg of platinum acetylacetonate.
[0084] Example 6
[0085] (1) 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in diethylenetriamine: oleylamine in volume ratios of 1:5; 1:2; 1:1; 2:1.
[0086] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat at 200°C for 3 hours.
[0087] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0088] Figure 8 Platinum nanocrystals were prepared by varying volume ratios of diethylenetriamine (DETA) and oleylamine (OAm) under a molybdenum hexacarbonyl (Mo(CO)6) content of 30 mg.
[0089] according to Figure 8When maintaining a molybdenum hexacarbonyl concentration of 30 mg, adding a small amount of oleylamine to dilute DETA did not result in significant banding; instead, a large number of lines were produced. Therefore, DETA should not be diluted. Using pure diethylenetriamine (DETA) as both a solvent and a surfactant is optimal.
[0090] Example 7
[0091] (1) Platinum nanoribbons were first synthesized by a solvothermal method. Typically, 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of DETA, with final concentrations of 2.12 mM and 18.93 mM, respectively.
[0092] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat it at 200°C for 30 min, 45 min, 60 min, 2.5 h, 3 h, and 6 h.
[0093] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0094] Figure 9 TEM images of platinum nanocrystals obtained at different reaction times: (a) 30 min; (b) 45 min; (c) 60 min; (d) 2.5 h; (e) 3 h; (f) 6 h.
[0095] The product was analyzed using a transmission electron microscope, such as Figure 9 As shown, after 30 min of reaction, only a small portion of grayish-white precipitate was collected, and only ultrafine particles (5 nm) were aggregated. Clearly, platinum reduction at such an early stage had only just begun. At 45 min, the captured intermediate contained small nanoparticles around 10 nm in size and a small amount of ultrafine nanowires. Some nanowires also had thickened tails. With increasing reaction time, the amount of precipitate increased slightly, mainly composed of ultrafine nanowires with diameters of 1–2 nm and lengths reaching tens of nanometers. These intermediates still contained nanoparticles and plates attached to the nanowires, as well as some ribbon-like structures, likely formed by the lateral extension of the nanowires. In subsequent reaction stages, the size and number of ribbon-like crystals gradually increased with increasing reaction time. After heating for 3 h, the product was mainly composed of plate-like and ribbon-like nanocrystals. Figure 9 e). Extend the reaction to 6 hours ( Figure 9 f) No further morphological changes were observed, possibly due to the depletion of the platinum precursor.
[0096] Example 8
[0097] (1) 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of DETA, and the final concentrations were 2.12 mM and 18.93 mM, respectively;
[0098] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml Teflon-lined autoclave and heat at 150°C for 1, 2, 3 and 6 hours.
[0099] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0100] Figure 10 Transmission electron microscopy (TEM) images of platinum nanocrystals prepared at 150 °C for different reaction times: (a) 1 hour; (b) 2 hours; (c) 3 hours; (d) 6 hours.
[0101] Transmission electron microscopy analysis of the product showed that when the reaction temperature was fixed at 150℃, extending the reaction time gradually consumed CO in the system. When the reaction time was extended from 1 hour to 6 hours, the platinum precursor first precipitated as gray-black platinum nanoparticles, which then grew into ultrafine one-dimensional platinum nanowires. Irregular pencil-shaped and hexagonal platinum nanosheets gradually appeared at the tips of these nanowires and underwent lateral epitaxial growth on some nanowires, eventually transforming them into platinum nanoribbons. This indicates that as the temperature decreases, the reaction rate further decreases, and a longer reaction time of 6 hours is required to generate platinum nanoribbons.
[0102] Example 9
[0103] (1) Platinum nanoribbons were first synthesized by a solvothermal method. Typically, 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of DETA, with final concentrations of 2.12 mM and 18.93 mM, respectively.
[0104] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml autoclave lined with Teflon and heat it at 120 ℃, 150 ℃, 160 ℃, 180 ℃, 200 ℃ and 240 ℃ for 3 hours respectively.
[0105] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0106] Figure 11TEM images of platinum nanocrystals synthesized using different reaction temperatures in this invention: (a) 120 ℃; (b) 150 ℃; (c) 160 ℃; (d) 180 ℃; (e) 200 ℃; (f) 240 ℃.
[0107] Transmission electron microscopy analysis of the product revealed that, to further accelerate the decomposition kinetics of molybdenum hexacarbonyl and the corresponding CO release rate, the reaction temperature was increased from 160℃ to 240℃. The increased temperature simultaneously accelerated CO generation and consumption, thus preferentially forming one-dimensional platinum nanowire bundles in the early stages of the reaction. Upon continuous heating, these nanowires fractured: longer fragments evolved into nanoribbons through lateral growth, while shorter nanowire fragments randomly grew into irregular nanosheets. Therefore, the optimal temperature for rapidly obtaining nanoribbons is 200℃; temperatures below this level result in one-dimensional linear growth, and no significant changes occur above 200℃.
[0108] Example 10
[0109] (1) 5 mg of platinum acetylacetonate (Pt(Acac)2) and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of DETA, and the final concentrations were 2.12 mM and 18.93 mM, respectively;
[0110] (2) Transfer the ultrasonically mixed solution from step (1) to a 10 ml autoclave lined with Teflon and react at 150°C for 3 hours, then transfer to 200°C for 3 hours.
[0111] (3) After cooling the high-pressure tank in step (2) to room temperature, wash the black precipitate collected from the high-pressure tank with ethanol and water several times, and then characterize it.
[0112] Figure 12 The reaction was carried out at 150 °C for 3 hours, then transferred to 200 °C for another 3 hours.
[0113] As can be seen from the circled part in the figure, there is banded growth, but because it reacts at 150 ℃ for 3 hours first, a large number of one-dimensional lines will be generated, which is not what we need. Therefore, this condition is not optimal.
[0114] Example 11
[0115] (1) 5 mg of Pt(acac)2 and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of diethylenetriamine (DETA) and the final concentrations were 2.12 mM and 18.93 mM, respectively;
[0116] (2) Transfer the ultrasonically dispersed solution from step (1) to a 10 ml Teflon-lined autoclave and heat it at 200°C for 3 hours.
[0117] (3) Take out the precipitate after the reaction in step (2), wash it with ethanol and water several times, and then characterize it.
[0118] Figure 13 Fourier transform infrared spectroscopy of DETA adsorption.
[0119] As shown in the figure, DETA, acting as a surfactant, is adsorbed onto the platinum surface. This demonstrates that DETA functions as both a solvent and a surfactant in this invention.
[0120] The synthesized platinum nanoribbons were washed multiple times with ethanol and water and dried in an oven at 80 °C. 1 mg of carbon powder was weighed and mixed with 4 mg of carbon powder. 1 ml of solvent was added and ultrasonically dispersed. 4 μL of the mixture was then dropped into a 3 mm diameter working electrode in two separate 2 μL drops for catalytic testing. The solvent was a mixture of ethanol and water in a 4:1 ratio with 2.5% naphthol added.
[0121] Electrochemical tests were then performed using a three-electrode system: a platinum sheet electrode as the counter electrode; a saturated calomel electrode (SCE) as the reference electrode; and a 3 mm diameter disc electrode as the working electrode. The electrolyte consisted of a 1 M KOH and a 1 M ethylene glycol aqueous solution. Cyclic voltammetry (CV) was performed at a scan rate of 50 mV / s, with the chronoamperometry (it) set to 25,000 s.
[0122] Figure 14 and Figure 15 When we use the platinum nanoribbons synthesized by the method in Example (1) and conventional commercial platinum carbon as ethylene glycol oxidation catalysts, we obtain the mass activity diagram by cyclic voltammetry (CV) and the stability results by chronoamperometry (it) stability test.
[0123] like Figure 14 and Figure 15 The results of cyclic voltammetry (CV) and chronoamperometry (it) stability tests are shown.
[0124] The results show that the mass activity of platinum nanoribbons reaches 2.86 mA / mg, while the areal activity of commercial Pt / C is only 0.79 mA / mg. Therefore, the current density of solution-grown platinum nanoribbons exhibits more than twice the catalytic efficiency for ethylene glycol oxidation compared to traditional commercial platinum-carbon. Platinum nanoribbons not only have significantly higher mass activity for ethylene glycol oxidation than commercial Pt / C, but also maintain considerable residual activity after a long-term test of 25,000 s. They combine excellent catalytic activity with resistance to poisoning, overcoming the shortcomings of insufficient activity and susceptibility to poisoning and deactivation of traditional Pt / C, and thus possess advantages in the application of anode catalysts for direct alcohol fuel cells.
[0125] This invention is not limited to the specific technical solutions described in the above embodiments. Any modification or equivalent substitution of this invention to achieve the same technical effect is within the scope of protection of this invention.
Claims
1. A simple one-step solvothermal method for synthesizing small-sized platinum nanoribbons, characterized in that... Includes the following steps: (1) Platinum acetylacetonate Pt(acac)2 and molybdenum hexacarbonyl Mo(CO)6 were uniformly dispersed in diethylenetriamine DETA, with final concentrations of 2.12 mM and 18.93 mM, respectively; (2) Transfer the ultrasonically dispersed solution from step (1) to a Teflon-lined autoclave and heat it at 150-240°C for 3-6 hours. (3) Take out the precipitate after the reaction in step (2), wash it with ethanol and water several times to obtain platinum nanoribbons.
2. The method for synthesizing small-sized platinum nanoribbons using a simple solvothermal method according to claim 1, characterized in that: In step (1), 5 mg of Pt(acac)2 and 30 mg of Mo(CO)6 solid powder were weighed and added simultaneously to 6 ml of diethylenetriamine DETA; Step (2) Transfer the liquid to a 10 mL Teflon-lined autoclave and heat it at 200°C for 3 hours. DETA can be adsorbed onto the platinum surface through reaction.
3. The method for synthesizing small-sized platinum nanoribbons using a simple solvothermal method according to claim 1, characterized in that... The nanoribbons are mostly elongated trapezoids, twisted hexagons, and squares; the longitudinal direction of the nanoribbons varies greatly, from 20 nm to 2 nm, and the width is relatively uniform, with an average width of 8.1 ± 1.9 nm. The precipitate after the reaction in step (2) was removed, washed repeatedly with ethanol and water, and then characterized.
4. The method for synthesizing long platinum nanoribbons in solution phase by a simple solvothermal method according to claim 1, characterized in that... Includes the following steps: (1) 5 mg of Pt(acac)2 and 30 mg of molybdenum hexacarbonylMo(CO)6 were uniformly dispersed in 6 mL of diethylenetriamine (DETA) and the final concentrations were 2.12 mM and 18.93 mM, respectively; (2) Transfer the ultrasonically dispersed solution from step (1) to a 10 ml Teflon-lined autoclave and heat it at 150°C for 6 hours. (3) Take out the precipitate after the reaction in step (2), wash it with ethanol and water several times, and then characterize it.
5. The method for synthesizing platinum nanoribbons in solution phase by a simple solvothermal method according to claim 1, characterized in that... Includes the following steps: (1) 5 mg of Pt(acac)2 and 30 mg of molybdenum hexacarbonyl (Mo(CO)6) were uniformly dispersed in 6 mL of diethylenetriamine DETA, and the final concentrations were 2.12 mM and 18.93 mM, respectively; (2) Transfer the ultrasonically dispersed solution from step (1) to a 10 ml Teflon-lined autoclave and heat it at 240°C for 3 hours. (3) Take out the precipitate after the reaction in step (2), wash it with ethanol and water several times, and then characterize it.
6. The application of the platinum nanoribbons prepared by any one of claims 1-5, characterized in that: Platinum nanoribbons can be used in fuel cells or electrochemical catalysis.
7. The application of the platinum nanoribbons prepared by the method according to claim 6, characterized in that... The synthesized platinum nanoribbon black precipitate was dried, mixed with carbon powder, and loaded onto a 3 mm diameter disc working electrode for catalytic testing.
8. The application of the platinum nanoribbons prepared by the method according to claim 6, characterized in that: Due to its unique structural features, this ribbon structure can be used in ethylene glycol fuel cells or proton exchange membrane batteries, exhibiting good electrocatalytic activity.